Agent-based organisational governance of services - Brazier, Frances M. T.; Dignum, Virginia; Huhns, Michael N.; Derksen, Christian; Dignum, Frank; Lessner, Tim; Padget, Julian A.; Quillinan, Thomas B.; Singh, Munindar P. (Multiagent and Grid Systems, 2012)
The objective of service-oriented computing (SOC) is to construct software applications out of appropriate services available and executing in place anywhere across the Web. To achieve this objective requires that techniques for discovering and engaging services be developed and used across the lifetime of the service-based applications. Succeeding with SOC in this broader sense presupposes that additional techniques be developed for ensuring desired quality of service metrics and service-level agreements. The crucial aspect of using services is thus their governance. In this paper, we describe a conceptual modelling approach that integrates organisational and coordination theories to achieve contextualised service governance. The approach allows for the development and analysis of dynamic, flexible, and robust service-oriented business applications.